Pengaruh Metode SQ3R Terhadap Maharah Al-Qiroah Siswa Kelas XI-3 SMA Mujahidin Surabaya - Ammar, Farikh Marzuki; Farobi, Faishol Ausi Al (LPPM Institut Pendidikan Nusantara Global, 2024)
The methods used in the learning process greatly influence student learning outcomes. Therefore, it is very important to pay attention. The article aims to determine the significant influence of the SQ3R method on al maharah al-qiraah in class XI-3 at SMA Mujahidin Surabaya. By using a quantitative approach with a quasi-experimental method. The implementation in class XI-3 of SMA Mujahidin Surabaya consisted of an experimental group (XI-3), totaling 20 students and a control group (XI-4), totaling 21 students. Data was collected through the use of final tests (post tests) and also observation. After this stage, analysis was carried out by comparing the average scores between the experimental group and the control group. Apart from that, the significance of the average value of the processed post-test results was also observed. This research resulted in the finding that the increase in learning outcomes for students in class XI-3 (experimental group) towards maharah al-qiraah was higher compared to students in class. Based on these results, the final average score for the class conventional method (lecture) is 76.00. Then, from the results, the conclusion is that the SQ3R method has a significant effect on maharah alqiraah in Arabic language learning for class XI-3 students.